Numerical analysis of thermal deformation and residual stress in automotive muffler by MIG welding. Issue 4 (14th May 2018) - Lee, S.H.; Kim, E.S.; Park, J.Y.; Choi, J.
Graphical Abstract: Abstract: In the automotive industry, metal inert gas (MIG) of welding technology is widely used for automotive muffler fabrication. However, the muffler is distorted by thermal deformation during the welding process. In this paper, the prediction of MIG welding-induced deformation and residual stress are simulated by SYSWELD software. The cross-section shapes of the molten pool predicted by the numerical analysis are compared to the experimental results. In the results of the stress, while compressive stresses are produced in regions away from the weld, high tensile stresses are produced in regions near the weld. Deformation values are calculated as 2.5 mm. The location of the actual welding deformation was similar to the experimental results. Based on the results, the methods to optimize the welding procedure will be provided by SYSWELD to improve muffler productivity.